Answer:
see explanation
Explanation:
Given
c = (s +
) m
There are 2 possible approaches
Approach 1
Divide both sides by m
= s +

Multiply both sides by 3 to clear the fraction
= 3s + b ( subtract b from both sides )
- b = 3s ( divide both sides by 3 )
-
= s, cancelling the factor 3 gives
s =
-

----------------------------------------------------------------------------------------
Approach 2
Distribute the right side by m
c = ms +

Multiply through by 3 to clear the fraction
3c = 3ms + bm ( subtract bm from both sides )
3c - bm = 3ms ( divide both sides by 3m )
-
= s, thus
s =
-
